Fluorescence response of a thiazolidine carboxylic acid derivative for the selective and nanomolar detection of Zn(ii) ions: quantum chemical calculations and application in real samples. Issue 127 (14th December 2015) - Balakrishnan, C.; Theetharappan, M.; Natarajan, Satheesh; Thalamuthu, S.; Neelakantan, M. A.
Abstract : A turn-on fluorescent sensor (L) for Zn 2+ detection in nano molar scale was synthesized and characterized. L shows fluorescence with Klebsiella pneumonia and E. coli . L was utilized to detect Zn 2+ ions and bacteria in environmental water samples. Abstract : A thiazolidine carboxylic acid derivative (L) was conveniently synthesized and characterized by spectral techniques and single crystal X-ray crystallography. The complexation of L with zinc (L–Zn 2+ ) was studied by scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) and further substantiated by 1 H NMR and ESI-MS analysis. The L showed excellent specificity and sensitivity towards a zinc-induced fluorescence response by forming a 1 : 1 complex (Job's plot) in a 95% (v/v) water–methanol mixture. The presence of zinc ions causes ∼40 fold fluorescence enhancement at 481 nm (quantum yield, Φ = 0.19) and can be detected with the naked eye under a UV-lamp. The L can detect Zn 2+ in nanomolar levels (13.90 nM) with good tolerance in the presence of other interfering metal ions. The reversibility of L–Zn 2+ complexation was checked by EDTA titration. The maximum fluorescence enhancement by Zn 2+ binding of L was observed in the pH range of 7.0–9.0. The dissociation constants of L and the stability constant of the L–Zn 2+ complex in 0.15 M NaClO4 were determined by pH metrically. Theoretical calculations were done using density functional theory (DFT) to support the above findings. L was successfully applied for the determination of Zn 2+ in water samples. The compound (L) detects the presence of, Klebsiella pneumoniae and E. coli in water samples.